GRAF PRIMA KOPRIMA ATAS GRUP DIHEDRAL - Shofiyulloh, M.; Munandar, Arif; Wardati, Khurul (Universitas Jenderal Soedirman, 2024)
A coprime prime graph over a finite group is a representation of a finite group on a graph by viewing group members as vertices of the graph and two distinct vertices and are adjacent if and only if order and order are prime or mutually prime. This research examines how to characterize the coprime prime graph over the dihedral group. Through analysis of the patterns that appear in the graphs formed, properties of coprime prime graphs over dihedral groups can be found, especially those related to the characterization of complete graphs and Hamiltonian graphs. This research also discusses the vertex connectivity of the coprime prime graph over the dihedral group.